Cortical dynamics of acoustic and phonological processing in speech perception. - Linjun Zhang (Public Library of Science (PLoS), 2011)
In speech perception, a functional hierarchy has been proposed by recent functional neuroimaging studies: core auditory areas on the dorsal plane of superior temporal gyrus (STG) are sensitive to basic acoustic characteristics, whereas downstream regions, specifically the left superior temporal sulcus (STS) and middle temporal gyrus (MTG) ventral to Heschl's gyrus (HG) are responsive to abstract phonological features. What is unclear so far is the relationship between the dorsal and ventral processes, especially with regard to whether low-level acoustic processing is modulated by high-level phonological processing. To address the issue, we assessed sensitivity of core auditory and downstream regions to acoustic and phonological variations by using within- and across-category lexical tonal continua with equal physical intervals. We found that relative to within-category variation, across-category variation elicited stronger activation in the left middle MTG (mMTG), apparently reflecting the abstract phonological representations. At the same time, activation in the core auditory region decreased, resulting from the top-down influences of phonological processing. These results support a hierarchical organization of the ventral acoustic-phonological processing stream, which originates in the right HG/STG and projects to the left mMTG. Furthermore, our study provides direct evidence that low-level acoustic analysis is modulated by high-level phonological representations, revealing the cortical dynamics of acoustic and phonological processing in speech perception. Our findings confirm the existence of reciprocal progression projections in the auditory pathways and the roles of both feed-forward and feedback mechanisms in speech perception.